2019
DOI: 10.1080/24749508.2019.1600910
|View full text |Cite
|
Sign up to set email alerts
|

Survival, growth, aboveground biomass, and carbon sequestration of mono and mixed native tree species plantations on the Coromandel Coast of India

Abstract: In India, reforestation programs with native indigenous tree species are a recent activity. Information on experiences comparing mono-and mixed-species plantations is limited. This study aims to estimate growth, aboveground biomass, and carbon sequestration between the mixed-species plantation and mono-species plantation. The growth, survival, height, aboveground biomass, and carbon sequestration of 82 native mixed species plantations were compared with Casuarina equisetifolia an exotic species planted in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 49 publications
(50 reference statements)
0
3
0
1
Order By: Relevance
“…The positive effects of USR on SOC sequestration (Figure 2a) can be ascribed to high diversity leading to higher production of aboveground and root biomass, enhancing SOC input (Cong et al, 2014). Although some small‐scale observations and N‐addition experiments revealed negative relationships between diversity and productivity (Jiang et al, 2009), many studies have confirmed the positive diversity–productivity relationship in forests and grasslands (Anbarashan et al, 2020; Cong et al, 2014; Fornara & Tilman, 2009; Hulvey et al, 2013; Steinbeiss et al, 2008). The positive effects of diversity on productivity may be even higher in naturally assembled communities than manipulative experiments (Flombaum & Sala, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The positive effects of USR on SOC sequestration (Figure 2a) can be ascribed to high diversity leading to higher production of aboveground and root biomass, enhancing SOC input (Cong et al, 2014). Although some small‐scale observations and N‐addition experiments revealed negative relationships between diversity and productivity (Jiang et al, 2009), many studies have confirmed the positive diversity–productivity relationship in forests and grasslands (Anbarashan et al, 2020; Cong et al, 2014; Fornara & Tilman, 2009; Hulvey et al, 2013; Steinbeiss et al, 2008). The positive effects of diversity on productivity may be even higher in naturally assembled communities than manipulative experiments (Flombaum & Sala, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Open green spaces were analyzed with a holistic approach, and a multi-dimensional framework (ecological, recreational, and disaster oriented) was presented, emphasizing its integration with spatial planning by Senik and Uzun [29]. According to Anbarashan et al [30], mixed-species plantings had higher values of carbon sequestration than mono plantations. Vasagadekar et al [31] studied urban trees not only for beauty and aesthetic purposes but also for their carbon sequestration potential to combat climate change at the local level.…”
Section: Biomass Content and Carbon Sequestrationmentioning
confidence: 99%
“…55% of forest plantation area [5,6]. This species has wide uses mainly for timber, plywood, fuel wood, poles production, live hedges and carbon sequestration [7][8][9]. These myriad uses has caused a surge in demand for propagation by seed [10].…”
mentioning
confidence: 99%